The role of social insurance schemes in addressing the risks faced by agricultural workers in the Middle East and North Africa - Lucas Sato; Nourjelha Mohamed (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This Research Report, the first in in the series "Expanding social insurance for agricultural workers in Middle East and North Africa (MENA): Identifying key constraints and discussing policy options", focuses on exploring the most adequate social insurance benefits and features capable of addressing the main risks facing agricultural workers in the MENA region.
Keywords: 330; social insurance; social protection; agricultural workers; MENA